The Implementation of Islamic Consumption in Islamic Boarding School Residents - Besse Khusnul Khatimah; Edi Cahyono (PT Mattawang Mediatama Solution, 2023)
This study aims find Islamic consumption patterns regarding halal and toyyib aspects, simplicity in consumption, and income redistribution implemented by residents of Islamic boarding schools, especially residents of Hidayatullah Islamic boarding schools in Towuti.This research used descriptive qualitative method where data collection was carried out using triangulation method. The participants in this study were limited to residents of the Hidayatullah Islamic Boarding School who belonged to the Towuti Mushida group. The results of this study indicate that the residents of the Hidayatullah Islamic Boarding School in Towuti are trying to apply a halal and toyiban consumption pattern, live with a simple life, and share or help each other based on the advice in Islam.